Intraindividual comparison between open and endoscopic release in bilateral carpal tunnel syndrome: a meta‐analysis of randomized controlled trials. Issue 3 (16th February 2016) - Hu, Kejia; Zhang, Tiansong; Xu, Wendong
Abstract: Purpose: This study evaluated functional outcomes and safety after endoscopic and open bilateral carpal tunnel syndrome release in opposite hands of the same patients through a meta‐analysis of randomized controlled trial data. Materials and Methods: Randomized controlled trials involving both methods in opposite hands of patients with bilateral carpal tunnel syndrome were identified via a systematic review of PUBMED and EMBASE. Results: Relative risks (RRs) and 95% confidence intervals (CIs) from five randomized controlled trials involving 142 patients with bilateral carpal tunnel syndrome were calculated using fixed‐ or random‐effect methods, with a length of follow‐up from 24 to 52 weeks after surgery. Compared with open release, endoscopic carpal tunnel release was associated with significantly better Boston Carpal Tunnel Questionnaire functional status scores (mean difference [MD] = 0.13, 95% confidence interval [CI] [0.02 – 0.25]; P = 0.02), but not symptom severity scores (RR = 0.06, 95% CI [−0.15 to 0.04]; P = 0.25). Endoscopic release required a longer operative time, but the procedures did not differ significantly in visual analog scale pain scores (MD = 0.02, 95% CI [−0.08 to 0.11]; P = 0.75), handgrip strength (MD = 0.17, 95% CI [−2.03 to 2.37]; P = 0.88), digital sensibility static two‐point discrimination (MD = 0.34, 95% CI [−0.03 to 0.70]; P = 0.07), or complication rates (MD = 0.01, 95% CI [−0.02 to 0.05], P = 0.47). Conclusion: From intraindividual evidence, endoscopic release promoted better recovery of daily life functions than open release, but required a longer operative time. The procedures provided similar symptom relief and hand strength and sensibility recovery, and were safe for patients with carpal tunnel syndrome. Abstract : We conducted a database search and meta‐analysis of randomized controlled studies to compare the efficacy, safety, and outcomes of the gold standard open carpal tunnel release (OCTR) procedure with the newer, less invasive endoscopic carpal tunnel release (ECTR) procedure, which were performed on opposite hands in patients with bilateral carpal tunnel syndrome.